2018
DOI: 10.1002/chem.201804658
|View full text |Cite
|
Sign up to set email alerts
|

Activating the MoS2 Basal Plane by Controllable Fabrication of Pores for an Enhanced Hydrogen Evolution Reaction

Abstract: Molybdenum disulfide has drawn persistent interest as a promising nonprecious electrocatalyst alternative to Pt for the hydrogen evolution reaction (HER). However, the MoS2 catalytic efficiency is still lower than the Pt‐based catalysts owing to insufficient active sites with more inert basal planes. Herein, we designed and synthesized porous MoS2 nanosheets to activate the basal planes by etching away Al in Al‐doped MoS2. The optimized porous MoS2 shows a small onset overpotential as low as 136 mV, a large ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Hence, among the various alternative processes, the electrochemical reduction method is considered to be effective to produce H 2 on a larger scale. The advantage of this hydrogen evolution reaction (HER) by electrochemical process is its simplicity and high stability. , A desirable cathodic H 2 reaction needs good electroactivity, stability, high surface area, and operability at a low potential. To reduce the overpotential of water electrolysis, the same is done by manipulation of the electrolyte and electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, among the various alternative processes, the electrochemical reduction method is considered to be effective to produce H 2 on a larger scale. The advantage of this hydrogen evolution reaction (HER) by electrochemical process is its simplicity and high stability. , A desirable cathodic H 2 reaction needs good electroactivity, stability, high surface area, and operability at a low potential. To reduce the overpotential of water electrolysis, the same is done by manipulation of the electrolyte and electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the presence of both Mo 3+ and Mo 4+ in the SnS 2 -MoS 2 , implying a structural vacancy on its surface. 32 The peak of MoS 2 at 225.7 eV belongs to the S 2s peak of the Mo−S bond. Following the introduction of Sn, this peak divides into two separate peaks at 225.4 and 226.5 eV, which belong to the Mo−S bond and Sn−S bond in the SnS 2 -MoS 2 bond, respectively.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…It has been observed that throughout the doping and etching method, one can successfully activate the basal plane of MoS 2 by introducing pores, thus increasing its surface area. In this regard, Geng et al 64 designed Al–MoS 2 nanosheets by doping different amounts of aluminium (Fig. 3a–d), followed by the traditional one-step hydrothermal method.…”
Section: Fabrication Strategies Toward Basal Plane Activation Of Mos2mentioning
confidence: 99%